The Relationship Between Contact With Pets And Domestic Animals And Their Owners' Mental Health And Personality Trait - Ali Taheri Mirghaed; Masoud Yunesian; Hossein Dargahi; Alireza Bahonar; Alireza Bahrami; Amir Lalehgani; Hamid Choobineh (Tehran University of Medical Sciences, 2013)
Background and Aim: Today, many families either have pets or work in animal husbandry units. It is very important to investigate the mental outcomes of animal care and also to study their keepers' personality traits. This study aims to perform a comparative examination of owners' mental health and character specifications or those of animal husbandry units' personnel.  Materials and Methods: In this descriptive study, about 500 people were selected through available sampling technique. They had contact with animals or worked in a husbandry unit in the suburbs of Tehran. After referring to the veterinary clinic of Tehran University, they were studied using a general health questionnaire and an international personality question bank. The collected data were analyzed using SPSS software as well as multivariate and follow-up tests. Results: The results of the present study show that all general mental health sub-scales except for anxiety are different in these groups. However, no difference was observed regarding responsibility and extroversion. Meanwhile, the adaptability of dog owners was lower than that of sheep owners; moreover, cattlemen were more irritable than sheep owners. Conclusion : In sum, the mental health of pet owners of the present study is at a lower level compared to that of those in other countries. It seems that the difference is due to religious and cultural differences existing between the two.